ANALISIS DETERMINAN TENAGA KERJA TERDIDIK YANG BEKERJA PADA LAPANGAN PEKERJAAN NON PRIMER DI SUMATERA BARAT - Krismay Putri; Hasdi Aimon (Universitas Negeri Padang, 2019)
This study explain the determinants of educated workforce who work on the non primary employment in West Sumatra.The data used is cross section in 2018. The variables used this study are non primary employment, educated, age, work experience, residence and gender. This model uses multiple logistic regression analysis. The result shows tha: 1) educated hasQa positiive and siignificant efffect on the non pimary employmeent 2) age of workforce educated hasYa poositive and not siignificant effect on the non primary employment. 3) work experiience has a possitive and siignificant efffect on the non primary employment 4) residence has a positive and significant effect on the non primary employmen. 5) gender haas a poositive and siignificant effeect on the non primary eemployment.